Transmission through Surface Disordered Waveguides and Nanowire as Drastic Influence on Coherent Scattering (Bulletin of Pure and Applied Sciences – Physics, 2019)
We have studied transmission through surface disordered waveguides in general and  a solid basis. Our results showed that desired transmission properties on a waveguide  through the roughness of its boundaries can be obtained. This surface scattering  approach predicted that how mode specific scattering lengths in waveguides depend  on the details of system’s surface roughness. It was shown that previously neglected square-gradient scattering mechanism and predicted that this new scattering  mechanism has to be considered together with the conventional amplitude scattering  mechanism. Square gradient scattering is related to higher order terms in the disorder  strength it can be the major scattering mechanism in system with modest disorder.  Surface scattering theory is for long range correlations, which seems to restrict its  applicability to very long waveguides. We have extended this surface scattering  theory to short, individual waveguides. We found that an observed shift of the  amplitude scattering gap could be attributed to the nonvanishing disorder strength.  We also found that short wave lengths can exhibit effects predicted for systems with  long range correlations leading to drastic changes in their transmission properties.  The obtained results were compared with previously obtained results of theoretical  and experimental works and were found in good agreement.